Artilce Assessment of Basic Education Graduates Competencies Acquired in Business Studies for Self-Reliance in Postikum Metropolis, Yobe State, Nigeria - Munkaila Abubakar Garba; Mohammad Adam; Adamu Ibrahim (Journal of Vocational Education Studies, 2022)
The study “Assessed basic education graduates’ competencies acquired in business studies for self-reliance in Postikum metropolis, Yobe state, Nigeria” Five specific objective, five research questions and five null hypotheses guided the study. The study adopted outcome evaluation research design. The study had population of 11,922 basic education graduates and 100 were randomly selected and used for the study. The instrument used for data collection was practical exercise adopted from previous examinations. The instrument was validated by two experts and pilot tested. A reliability coefficient of 0.78 was obtained. Five research assistants helped in the data collection. The data collected were analyzed using descriptive statistic of mean and standard deviation to answer the research questions while Independent-Sample t-test was used to test the null hypotheses at 0.05 level of significance. The study revealed that among others that the extent to which business studies provide basic education graduates with Keyboarding, Computer, Accounting and Shorthand skill was very low for self- reliance in Potiskum metropolis, Yobe State. It was concluded that the philosophy of introducing business studies at basic education level to reduce the rate of unemployment among the graduates will not be achieved if the students continue to graduate without requisite skills in keyboarding, Shorthand, Computer, Marketing and Accounting skills. The study recommended among others that Basic education students should be exposed to more practical in keyboarding, marketing and accounting that will enable them acquire needed skills for self-reliance upon graduation.